2022
DOI: 10.3390/ncrna8010017
|View full text |Cite
|
Sign up to set email alerts
|

miR-294 and miR-410 Negatively Regulate Tnfa, Arginine Transporter Cat1/2, and Nos2 mRNAs in Murine Macrophages Infected with Leishmania amazonensis

Abstract: MicroRNAs are small non-coding RNAs that regulate cellular processes by the post-transcriptional regulation of gene expression, including immune responses. The shift in the miRNA profiling of murine macrophages infected with Leishmania amazonensis can change inflammatory response and metabolism. L-arginine availability and its conversion into nitric oxide by nitric oxide synthase 2 (Nos2) or ornithine (a polyamine precursor) by arginase 1/2 regulate macrophage microbicidal activity. This work aimed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…With these facts in mind, we attempted to study the expression of macrophage metabolism-related genes upon supplementation with putrescine, spermidine and spermine, with or without L-arginine during infection. After L- We have already reported that higher levels of citrulline in BALB/c and C57BL/6 macrophages after 4h of infection with L. amazonensis did not correlate with NO production, once the NO production was observed only in C57BL/6 macrophages (35,45,47). We now showed that the supplementation with putrescine increased Nos2 levels, but did not reflect in increased NO production.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…With these facts in mind, we attempted to study the expression of macrophage metabolism-related genes upon supplementation with putrescine, spermidine and spermine, with or without L-arginine during infection. After L- We have already reported that higher levels of citrulline in BALB/c and C57BL/6 macrophages after 4h of infection with L. amazonensis did not correlate with NO production, once the NO production was observed only in C57BL/6 macrophages (35,45,47). We now showed that the supplementation with putrescine increased Nos2 levels, but did not reflect in increased NO production.…”
Section: Discussionmentioning
confidence: 56%
“…We have already reported that higher levels of citrulline in BALB/c and C57BL/6 macrophages after 4h of infection with L. amazonensis did not correlate with NO production, once the NO production was observed only in C57BL/6 macrophages (35,45,47). We now showed that the supplementation with putrescine increased Nos2 levels, but did not reflect in increased NO production.…”
Section: Discussionmentioning
confidence: 87%
“…skin lesions, probably by the low O 2 pressure in the micromilieu [65]. However, we have already reported NO production in L. amazonensis infected C57BL/6 macrophages [39,50,66]. NO-producing cells were observed in L-arginine plus spermine supplementation in L. amazonensis-infected macrophages without Nos2 modulation.…”
Section: Plos Onementioning
confidence: 77%
“…We showed here that, although early stages of photo-oxidative damage (1-day) do not show substantial histological changes, there are already detectable miRNA changes in the circulation. These miRNAs included miR-128a-3p, miR-200b-3p, miR-410-3p and miR-218-5p, which have shown to be involved in inflammation and oxidative stress processes and to play a role in neurodegenerative disorders including AMD Wu et al, 2020;Xiong et al, 2021;Yang et al, 2021;ElShelmani et al, 2021a;Acuña et al, 2022). This suggests that their presence in circulation reflects early changes in retinal homeostasis and we hypothesize that these miRNAs have the potential to be early indicators of disease onset.…”
Section: Circulating Mirnas Are Linked To Photoreceptor Degenerationmentioning
confidence: 91%